2021
DOI: 10.3390/insects12060520
|View full text |Cite
|
Sign up to set email alerts
|

Effects on Brood Development in the Carpenter Ant Camponotus vicinus Mayr after Exposure to the Yeast Associate Schwanniomyces polymorphus Kloecker

Abstract: The yeast Schwanniomyces polymorphus is associated with the infrabuccal pocket in the carpenter ant Camponotus vicinus (Hymenoptera: Formicidae), but its role in ant development is poorly defined. The potential effects of this yeast on brood development were examined on sets of larval groups and workers over a 12 week period. Worker–larval sets were fed variations of a completely artificial, holidic diet and exposed or not exposed to live S. polymorphus. Worker–larval sets in half of the experiment were defaun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…Previously, this was the most frequently isolated species from rotting wood samples collected at Atlantic rainforest in Brazil in YNB‐xylan and YNB‐xylose (Morais et al, 2013). This species is also associated with the infrabuccal pocket of the carpenter ant Camponotus vicinus (Hymenoptera: Formicidae), but its role in ant development is not clear (Mankowski et al, 2021). While Schw.…”
Section: Resultsmentioning
confidence: 99%
“…Previously, this was the most frequently isolated species from rotting wood samples collected at Atlantic rainforest in Brazil in YNB‐xylan and YNB‐xylose (Morais et al, 2013). This species is also associated with the infrabuccal pocket of the carpenter ant Camponotus vicinus (Hymenoptera: Formicidae), but its role in ant development is not clear (Mankowski et al, 2021). While Schw.…”
Section: Resultsmentioning
confidence: 99%
“…Other authors have reported the presence of bacteria and yeasts from infrabuccal pockets of various ant species. These microorganisms were found at higher levels in the pocket compared to nest material and soil outside of nests, although their potential role in the digestion of nutrients or population immunity remains unknown although two of the studies indicated a nutritional role of an infrabuccal yeast in Camponotus vicinus (Mankowski and Morrell, 2004;Pagnocca et al, 2008;Mankowski et al, 2021). Recent studies in two predatory ponerine species (Zheng et al, 2021) and species that feed on honeydew (Zheng et al, 2022) showed that the bacterial composition in the infrabuccal pocket is related with diet.…”
Section: Discussionmentioning
confidence: 99%
“…These studies also showed that the contents of the pocket accumulated as pellets that are regurgitated on a daily basis. Hansen et al (1999) and Mankowski et al (2004Mankowski et al ( , 2021 noted the presence of bacterial and yeast cells in the infrabuccal pocket of Camponotus modoc and Camponotus vicinus.…”
Section: Introductionmentioning
confidence: 99%
“…Among the benefits of insect–yeast relationships are the provision of essential nutrients to both yeasts and insects, improved digestion of insect recalcitrant diets, provision of suitable hybridization habitats for yeasts, and facilitation of yeast dispersal from one sugar source to another in ephemeral habitats such as the annual ripening of fruits (Reuter et al, 2007; Stefanini, 2018). The transfer of specific mutualistic and symbiotic yeast species from maternal insect parents to their offspring further highlights the extent of these associations (Mankowski et al, 2021; Rosenblueth et al, 2018; Salem et al, 2015). Insects such as honeybees, termites, butterflies, moths, beetles, and mosquitoes have been found to harbor diverse yeast species (Stefanini, 2018).…”
Section: Introductionmentioning
confidence: 99%